STRUTUR FISIK PANTUN PADA BUKU 1001 PANTUN UNTUK ANAK - Karimatuzzahra Karimatuzzahra; Syafrial Syafrial; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study has the title Pantun Physical Structure in the 1001 Pantun Book for Children. The background to this research is that the researchers wanted to see the quality of the physical structure of the pantun in book 1001 Pantun for Children? The aim of this study was to determine the quality of the physical structure of the pantun in book 1001 Pantun for Children. This research is a research into mixing methods using two research methods. Quantitative is used to analyze data and qualitatively used to draw conclusions. On the basis of the research, the rhyme gets an average score of 25, no sampiran gets the maximum score of 40. The content of the pantoen as a whole, totaling 286 pantun, gets a score of 25. The following is the rhymes. A total of 271 rhymes gets a score of 20, 12 rhymes get a score of 25, and only 3 rhymes get a maximum score of 30.Key Words: Structure, physical, rhyme